Non-invasive management of severe subcutaneous emphysema in a pediatric asthma exacerbation: a case report and review - Amal H. Aljohani; Hamdi Alsufiani; Ghousia Ahmed (International Journal of Emergency Medicine)
Abstract Background Spontaneous pneumomediastinum (SPM) and subcutaneous emphysema (SE) are rare, severe, and potentially life-threatening complications associated with asthma exacerbation. Most of these conditions are benign and self-limiting. However, the overlapping symptoms between asthma exacerbation and pneumomediastinum (PM) may delay diagnosis. These conditions can usually be managed through conservative treatment, although unfamiliarity with this presentation may lead some physicians to consider surgical intervention. Case presentation We report a unique case involving a 9-year-old patient experiencing a severe bronchial asthma attack and right lobe atelectasis complicated by PM and severe SE that extended to his left eye. The condition was successfully treated conservatively, with aggressive management of asthma exacerbation and close monitoring in the intensive care unit. Conclusion This case highlights the effectiveness of conservative management of PM and SE with appropriate asthma exacerbation treatment. Early diagnosis and management can lead to a favorable prognosis and a relatively brief hospital stay. Clinical trial number Not applicable.